Incidence and prevalence of sporadic and hereditary MTC in Denmark 1960–2014: a nationwide study. Issue 6 (June 2018) - Mathiesen, Jes Sloth; Kroustrup, Jens Peter; Vestergaard, Peter; Stochholm, Kirstine; Poulsen, Per Løgstrup; Rasmussen, Åse Krogh; Feldt-Rasmussen, Ulla; Schytte, Sten; Londero, Stefano Christian; Pedersen, Henrik Baymler; Hahn, Christoffer Holst; Djurhuus, Bjarki Ditlev; et al.
Abstract : Recent studies have shown a significant increase in the temporal trend of medullary thyroid carcinoma (MTC) incidence. However, it remains unknown to which extent sporadic medullary thyroid carcinoma (SMTC) and hereditary MTC (HMTC) affect the MTC incidence over time. We conducted a nationwide retrospective study using previously described RET and MTC cohorts combined with review of medical records, pedigree comparison and relevant nationwide registries. The study included 474 MTC patients diagnosed in Denmark between 1960 and 2014. In the nationwide period from 1997 to 2014, we recorded a mean age-standardized incidence of all MTC, SMTC and HMTC of 0.19, 0.13 and 0.06 per 100, 000 per year, respectively. The average annual percentage change in incidence for all MTC, SMTC and HMTC were 1.0 ( P = 0.542), 2.8 ( P = 0.125) and −3.1 ( P = 0.324), respectively. The corresponding figures for point prevalence at January 1, 2015 were 3.8, 2.5 and 1.3 per 100, 000, respectively. The average annual percentage change in prevalence from 1998 to 2015 for all MTC, SMTC and HMTC was 2.8 ( P < 0.001), 3.8 ( P < 0.001) and 1.5 ( P = 0.010), respectively. We found no significant change in the incidence of all MTC, SMTC and HMTC possibly due to our small sample size. However, due to an increasing trend in the incidence of all MTC and opposing trends of SMTC (increasing) and HMTC (decreasing) incidence, it seems plausible that an increase for all MTC seen by others may be driven by the SMTC group rather than the HMTC group.